Financing of working capital requirement, financial flexibility and SME performance - Baños-Caballero, Sonia; García-Teruel, Pedro J.; Martínez-Solano, Pedro (Journal of Business Economics and Management, 2016)
This paper investigates the relation between the financing strategies of working capital requirement and firm performance for the period 1997 to 2012. Using the two-step generalized method of moments estimator, we find that a suitable financing strategy can help firms improve their performance. Moreover, the results indicate that the working capital requirement financing-performance relation changes during a financial crisis. Finally, we also find that this relation depends on a firm’s financial flexibility. The findings are of interest for managers and researchers and show that managers should not only be concerned about investing in working capital requirement but also consider how this investment is to be financed. To the best of our knowledge, this is the first paper to analyse how the financing strategy selected by firms to finance their working capital requirement affects their performance.